2009
DOI: 10.1111/j.1468-2982.2009.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting airplane headache in a patient with chronic rhinosinusitis

Abstract: The authors report long-lasting airplane headache in a patient with non-allergic, chronic rhinosinusitis. Association of mucosal inflammation with compromised sinonasal ventilation and sinus barotrauma created a base for not only the pain but also for the prolongation of symptoms. Effective therapy with antihistamine and nasal decongestant supports the theory that sinonasal barotrauma plays a triggering role in the pathophysiology of airplane headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Pfund et al have suggested that impaired sinonasal ventilation and sinus barotrauma due to mucosal inflammation create a base for not only the AH, but also for the prolongation of symptoms. Effective therapy with antihistamine and nasal decongestant supports the theory that sinonasal barotrauma plays a triggering role in the pathophysiology of AH [6]. Our first case also confirms this theory.…”
Section: Discussionsupporting
confidence: 84%
“…Pfund et al have suggested that impaired sinonasal ventilation and sinus barotrauma due to mucosal inflammation create a base for not only the AH, but also for the prolongation of symptoms. Effective therapy with antihistamine and nasal decongestant supports the theory that sinonasal barotrauma plays a triggering role in the pathophysiology of AH [6]. Our first case also confirms this theory.…”
Section: Discussionsupporting
confidence: 84%
“… • The authors stated that their effective treatment with antihistamine and anti-inflammatory medications support the theory that sinus barotrauma plays a central role in the mechanism of AH. 2010, Pfund et al [ 19 ] 1 1 F 27 Case report • The patient developed bilateral headache located in her ear, cheek, forehead, and on the top of the head. The pain was described as stabbing, jabbing and rated as 10/10.…”
Section: Resultsmentioning
confidence: 99%
“… • The authors supported the hypothesis of sinus barotrauma as a possible mechanism of AH. 2011, Mainardi et al [ 29 ] N/A N/A N/A Letter to the editor • The authors stated that the findings from the paper by Pfund et al [ 19 ] differ from the stereotypical AH-attacks: 1) The AH-attack does not exceed 30 min, 2) the pain is not strictly bilateral and 3) neuroradiological examinations do not show signs of sinus inflammation. • They suggested that “pure” AH should be considered as a separated headache from the flight-related headache in patients with organic condition.…”
Section: Resultsmentioning
confidence: 99%
“…7 In light of the literature, it has been observed that this pathology is related to sinus barotraumas, alterations in its pressure, personal history of acute or chronic sinusitis or allergies. 8 In 2012, Mainardi et al 9 performed a study with 75 patients where it was observed that the disease was more common in men (61.3%) over 35 years of age without symptoms in the first flight (88%). The predominant clinical was hemicranial headache (86.5%) fronto-orbital (76.7%), "hammering" (70.3%) and shorter than 30 minutes (95.8%) being the most frequent 10-20 minutes (58.3%).…”
Section: Discussionmentioning
confidence: 99%